Jñāneśvarī. mūḷa sãhitā, pāṭhabheda, prastāvanā, ṭīpā spashṭīkaraṇa, śabdakośa, va bhāshāśāstravishayaka pariśishṭāsaha - Jñānadeva, fl. 1290 (SAMP early 20th-century Indian books project ;, 1951)
Classical commentary on Bhagavadgītā, Hindu philosophical work; with interpretive notes.